National Legislative Frameworks for the Protection of Soil in Urban Areas in Serbia - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Soil represents one of the most important renewable resources, and its good quality and sustainable use are preconditions for the survival of numerous ecosystems on a global level. Irrational exploitation of natural resources, industrialisation and expansion of population in the cities contribute to the increase of soil pollution, particularly in the urban zones, which causes negative consequences on human health and the environment. That is the reason why the author of this paper briefly presents the current state of soil quality in larger cities in Serbia, with special focus on the presence of pollutants, as well as to analyse existing national legal frameworks relevant for the protection of soil from negative anthropogenic impacts, including preventive provisions, but also the norms of penal, i.e. criminal and misdemeanour law. In an attempt to contribute to the improvement of the state in this field, the author highlights the most important principles on the basis of which the legal protection of soil should be developed in Serbia, suggesting some innovative solutions regarding the incrimination of prohibited human activities, which may harm or endanger this eco-medium.